Wolbachia Infection in Two Species: Novel Views on the Colonization Ability of Wolbachia in Aphids. Issue 6 (23rd October 2019) - Chen, Rui; Su, Xiaomin; Chen, Jing; Jiang, Liyun; Qiao, Ge-Xia
Abstract: Wolbachia pipientis (Rickettsiales: Anaplasmataceae) is an intracellular symbiont residing in arthropods and filarial nematodes. Sixteen supergroups have been described from different host taxa. Four supergroups A, B, M, and N were found in aphids according to prior studies. The cotton aphid, Aphis gossypii, and the green peach aphid, Myzus persicae, are typical polyphagous species with global distributions. We conducted an extensive and systematic survey of Wolbachia infections in these aphids from China. High incidences of Wolbachia infection were detected. The total infection incidence was 60% in A. gossypii and 88% in M. persicae . Both aphid species were infected with supergroups A, B and M. Different incidences of infection were observed among the seven geographical regions in China, which suggested a positive relationship between Wolbachia infections and the geographical distribution of aphid species. Furthermore, multiple infection patterns (M, B, A&M, B&M, and A&B&M) were observed. Infection patterns M and B&M were detected in almost all populations. Patterns A&B&M and B showed geographical restriction in North China. Three factors can possibly influence the Wolbachia infection incidences and patterns: the geographical distribution, aphid species, and different supergroup types.